New Insights into the Semantics of Legal Concepts and the Legal Dictionary by Martina Baj?i? (2017), John Benjamins Publishing Company xi + 222pp - Mac Aodha, Mairtin (International Journal of Speech, Language and the Law, 2017)
New Insights into the Semantics of Legal Concepts and the Legal Dictionary by Martina Baj?i? (2017), John Benjamins Publishing Company xi + 222pp